The value of blood and urine metabolomics in differential diagnosis of cholestasis in infants - Samah Abdelfatah Eshiaty; Shimaa Abdelsattar; Dina Sweed; Samira A. Abdel-Aziz; Ashraf Elfert; Hala Elsaid (Egyptian Liver Journal, 2023)
Abstract Background Early detection of biliary atresia (BA) is a great challenge providing the main useful way to improve its clinical consequence. Promising metabolomics provides an effective method for determining innovative biomarkers and biochemical ways for improving early diagnosis. This study aimed to determine the benefit of serum and urinary potential bile acid metabolites in the differentiation of BA from non-biliary atresia (non-BA) cases using tandem mass spectrometry (MS/MS). Fourteen bile acids metabolites were measured quantitively by MS/MS in serum and urine samples from 102 cholestatic infants and 102 control infants, in addition to the assay of the total serum bile acid enzymatically. Results After the diagnostic clinical and laboratory workflow, cholestatic infants were divided into BA (37 infants) and non-BA (65 infants) subgroups. Remarkably on analysis of serum individual bile acid concentrations, there were significant differences between cholestatic BA and non-BA regarding serum (glycocenodeoxycholic acid (GCDCA), taurochenodeoxycholic acid (TCDCA), taurocholic acid (TCA), and GCDCA/chenodeoxycholic acid (CDCA) ratio) (p < 0.001, for all), while there was no significant difference between the two groups regarding serum level of (cholic acid (CA), glycocholic (GCA), or TCDCA/CDCA ratio). There were no significant differences in either the urinary individual bile acids or urinary primary bile acids (conjugated or unconjugated) between BA and non-BA. Further principal component analysis (PCA) analysis was done and receiver operating characteristic (ROC) analysis was performed using score plots of the positive factors in the first two principal components PC1 (CA, GCA, GCDCA, TCA, TCDCA) and PC2 (CA, CDCA, lithocholic (LCA), ursodeoxycholic acid (UDCA)) for establishing the differences between the two diseased groups and revealed that the area under the curve (AUC) for PC1 was (0.770) higher than AUC for PC2 (0.583) indicating that the positive components of PC1 may be potential biomarkers for differentiation between the two cholestatic groups. Conclusions Metabolomics of serum bile acid levels using tandem mass spectrometry might change the paradigm differentiating BA from non-BA saving patients from unnecessary invasive procedures.